Between a Rock and a Hard Place: Challenges in Enacting Procedural Justice in Resolving Sexual Harassment Complaints - Adikaram, Arosha S.; Kailasapathy, Pavithra (Faculty of Management & Finance, University of Colombo, 2021)
This paper aims to examine what impedes Human Resource Professionals’ (HRPs) ability to enact procedural justice in resolving complaints of sexual harassment by identifying the challenges and difficulties HRPs encounter in practice. We conducted semi-structured, indepth interviews with 35 HRPs from 30 companies in Sri Lanka, employing a qualitative research approach. We found that HRPs face numerous challenges in enacting procedural justice. They struggle with competing demands to legally safeguard the company while also being fair to the parties concerned. We also found that complainants, other parties connected to the complaint, or observers can perceive HRPs as unfair even when they adhere to procedural justice principles. Understanding these challenges will help address some of the loopholes in complaint handling processes and highlight the need for interventions such as training to mitigate or eliminate the challenges HRPs face in taking fairer actions.
Keywords: Procedural Justice; Sexual Harassment Complaints; Human Resource Professionals; Challenges; Training